Bimbingan Belajar Bahasa Inggris bagi Siswa-Siswi Sekolah Dasar - Susanto Susanto; Yahmun Yahmun (Universitas Maritim AMNI Semarang, 2024)
English tutoring program comes to provide the English tutor for elementary students as one strategy to improve quality of English communication. The purposes of this program were to introduce the basic materials for children and to pronounce the basic vocabularies and sentences related to the daily life.This program was held at RT 09 and RW 04 Ngrayung, Ngadirenggo Village Pogalan-Trenggalek (East Java) and the praticipants were 20 students of class 4-6. The program was done during 3 months. The method used consisted of socialization, workshop and tutorial.The results showed that the students were interested in learning English. In the early meetings, students found difficulties to pronounce the vocabularies. The students were able to pronounce after 3 meetings even some students still make mistakes. In learning English; students were active in playing games, singing, spelling, pronouncing and role play. The results of pre test showed that only one student passed in the test, while nineteen students failed. The average score was 57.35. This means that the students must follow the English program. The results of post test showed that twenty students passed in the test. It was shown in the individual score. The data revealed that 8 students got 60-69 while 12 students got 70-79. The average score was 70. Therefore; the English tutoring program for elementary students can improve their learning achievement in English.